PENDIDIKAN BERBASIS KOMPETENSI DALAM PERSPEKTIF AJARAN ISLAM - Abdul Rozak (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2021)
Competency-based education is education that emphasizes the abilities that must be possessed by graduates in a level of education. Article 1 paragraph 1 of the 2003 National Education System Law states that: